The development of tea blister caused by Exobasidium vexans in tea (Camellia sinensis) correlates with the reduced accumulation of some antimicrobial metabolites and the defence signals salicylic and jasmonic acids. (11th March 2015) - Mur, L. A. J.; Hauck, B.; Winters, A.; Heald, J.; Lloyd, A. J.; Chakraborty, U.; Chakraborty, B. N.
Abstract : Blister blight (causal agent, Exobasidium vexans ) is an economically devastating disease of tea ( Camellia sinensis ). To determine what metabolite changes occur with tea blister that could be linked to disease progression, metabolomic approaches were used on E. vexans infected tea from a Darjeeling (India) plantation. Samples were classified according to disease phenotypes, i.e. either healthy or at one of three stages of disease progression. Initial metabolite fingerprinting using Fourier transform infrared (FTIR) spectroscopy indicated that metabolite changes could be related to disease stage. Electrospray ionization mass spectrometry (ESI‐MS) highlighted caffeine and flavonoid metabolism changes as disease progressed. High‐performance liquid chromatography (HPLC) with online photodiode array detection and electrospray ionization‐tandem mass spectrometry (HPLC‐PDA‐ESI/MS n ) was used to characterize the caffeine, flavan‐3‐ol, flavone and flavonol profiles. There were increases in quercetin and kaempferol glucosides, kaempferol triglycosides and some catechin‐class antioxidants, but also substantial reductions in apigenin and myricetin glycosides and, particularly, caffeine as disease progressed. The content of important defence hormones, salicylic acid and jasmonic acid, was also reduced in blister blight diseased samples. Thus, E. vexans infections perturb defence signalling and reduce many potentially antimicrobial compounds, such as caffeine, to aid disease progression.